2015
DOI: 10.1007/s10900-015-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community Health Nurse-Led Intervention on Childhood Routine Immunization Completion in Primary Health Care Centers in Ibadan, Nigeria

Abstract: Immunization coverage of vulnerable children is often sub-optimal in many low- and middle-income countries. The use of a reminder/recall (R/R) system has been one of the strategies shown to be effective in improving immunization rates. In the resent study, we evaluated the effect of R/R and Primary Health Care Immunization Providers' Training (PHCIPT) intervention on routine immunization completion among 595 infants in Ibadan, Nigeria. The design was a group randomized controlled trial with Local Government Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…At all three time points, the percentage of children fully vaccinated with the relevant dose of polio, pentavalent, and pneumococcal vaccines was significantly higher in the intervention than the control group (<.001), and the delay in receiving the vaccinations was significantly less in the intervention than the control group (<.001). Another RCT by Brown et al [ 15 ] conducted in Nigeria identified increased coverage rates relative to the usual care when receiving phone call reminders 2 days and 1 day before a vaccination appointment (Relative risk 1.72, 95% CI 1.50-1.98). Uddin et al [ 16 ] similarly found that SMS reminders increased the odds of vaccination uptake in both urban and rural areas; odds ratio (OR) 2.3 (95% CI 1.1-5.5) and OR 3.6 (95% CI 1.5-8.9), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At all three time points, the percentage of children fully vaccinated with the relevant dose of polio, pentavalent, and pneumococcal vaccines was significantly higher in the intervention than the control group (<.001), and the delay in receiving the vaccinations was significantly less in the intervention than the control group (<.001). Another RCT by Brown et al [ 15 ] conducted in Nigeria identified increased coverage rates relative to the usual care when receiving phone call reminders 2 days and 1 day before a vaccination appointment (Relative risk 1.72, 95% CI 1.50-1.98). Uddin et al [ 16 ] similarly found that SMS reminders increased the odds of vaccination uptake in both urban and rural areas; odds ratio (OR) 2.3 (95% CI 1.1-5.5) and OR 3.6 (95% CI 1.5-8.9), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from a study in rural Nigeria where real-time phone call immunisation reminders significantly improved immunisation completion premised our intent to use automated calls 14. The Nigeria study found a 41% increase in immunisation completion 14.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological differences may explain effect size differences. While our study sent out two reminder calls 2 days and the day before the immunisation due date, the prior published study used two real-time reminder phone calls plus four recalls if immunisations were missed as the primary intervention 14. Furthermore, and likely of importance, is the absence of the human element in automated calls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited data looking into different perceptions and barriers that may affect SMS-based interventions for improvement in childhood RI in resource constraint settings [37].…”
Section: Resultsmentioning
confidence: 99%